Synergistic Effect of Manually Assisted Cough During Mechanical Insufflation-Exsufflation in Patients With Spinal Cord Injury - Lee, Chae Hyeon; Hyun, Sung Eun; Hur, Yong; Shin, Hyung-Ik (Respiratory care, 2024)
Mechanical insufflation-exsufflation (MI-E) and manually assisted cough are frequently employed cough augmentation methods for enhancing cough efficiency in individuals with cervical spinal cord injury (CSCI). This study aimed to evaluate the synergistic impact of combining manually assisted cough and MI-E on cough peak flow in subjects with CSCI and identify their related factors. Fifteen subjects with CSCI with cough peak flow > -270 L/min underwent 5 consecutive days of 5 cough augmentation sessions; cough peak flow during exsufflation and the total insufflation volume (TIV) during insufflation were measured. Only MI-E was administered on days 1 and 5, whereas on days 2-4 one MI-E-only session followed by 3 MI-E and manually assisted cough sessions was implemented followed by a fifth MI-E-only session. The cumulative and carry-over effects of increasing treatment sessions and any associated factor on cough peak flow during MI-E-assisted coughing were assessed using a linear mixed model (LMM) with repetitive air-flow measurements within the same participants. No cumulative or carry-over effects of manually assisted cough and MI-E were shown with the accumulation of treatment days or sessions. The LMM confirmed that using manually assisted cough (-0.283 L/s, < .001), TIV (-0.045 L/s, = .002), and the individual manually assisted cough variance (-0.022 L/s, = .01) significantly influenced cough peak flow. Estimated mean cough peak flows for MI-E with manually assisted cough and MI-E alone were -4.006 L/s (95% CI -4.237 to -3.775) and -3.723 L/s (95% CI -3.953 to -3.492), respectively, surpassing the initial voluntary cough peak flow without MI-E assistance (-1.65 ± 0.53 L/s). The use of manually assisted cough and amount of TIV correlated with improved cough peak flow, emphasizing the importance of adequate in-expiratory support. No carry-over effect was associated with using manually assisted cough, highlighting the need to combine MI-E with manually assisted cough for each MI-E treatment to achieve optimal cough effectiveness.